COMPETITION VS. MONOPOLY DIFFERENCES, ADVANTAGES AND UZBEKISTAN'S EXPERIENCE (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
This article presents a comparative analysis of competition and monopoly as two fundamental market structures in economic theory. Drawing on classical and contemporary economic literature, relevant Uzbek legislation, and recent statistical data, the study examines differences in pricing, output, innovation incentives, and consumer welfare between the two structures. The article also analyses Uzbekistan's ongoing antimonopoly reforms (2017–2024) and offers five targeted policy recommendations.